2013
DOI: 10.1002/grl.50902
|View full text |Cite
|
Sign up to set email alerts
|

Field‐aligned currents associated with dipolarization fronts

Abstract: [1] Current densities associated with dipolarization fronts (DFs) have been calculated in the geomagnetic tail using the curlometer technique applied to high-resolution magnetic field E B data obtained by the four Cluster spacecraft. We then use the relationto characterize the behavior of field-aligned current (FAC) during 25 DF events. Our results show that the magnitude of FAC density (J // ) ranges from 5 to 20 nA/m 2 , and they are observed in Northern and Southern Hemispheres flowing along both directions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 25 publications
10
59
5
Order By: Relevance
“…Different from previous studies that suggested that parallel currents and perpendicular currents are generally uniform across the DF (e.g., Fu et al, 2012a;Runov et al, 2011;Sun et al, 2013;Yao et al, 2013), we find that strong parallel currents only exist in the high-density side of the DF and perpendicular currents feature multiple peaks at the DF. Different from previous studies that suggested that parallel currents and perpendicular currents are generally uniform across the DF (e.g., Fu et al, 2012a;Runov et al, 2011;Sun et al, 2013;Yao et al, 2013), we find that strong parallel currents only exist in the high-density side of the DF and perpendicular currents feature multiple peaks at the DF.…”
Section: Summary and Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Different from previous studies that suggested that parallel currents and perpendicular currents are generally uniform across the DF (e.g., Fu et al, 2012a;Runov et al, 2011;Sun et al, 2013;Yao et al, 2013), we find that strong parallel currents only exist in the high-density side of the DF and perpendicular currents feature multiple peaks at the DF. Different from previous studies that suggested that parallel currents and perpendicular currents are generally uniform across the DF (e.g., Fu et al, 2012a;Runov et al, 2011;Sun et al, 2013;Yao et al, 2013), we find that strong parallel currents only exist in the high-density side of the DF and perpendicular currents feature multiple peaks at the DF.…”
Section: Summary and Discussioncontrasting
confidence: 99%
“…Such difference may stem from the fact that at electron scale, DF may be more like a nonlinear structure (e.g., Balikhin et al, 2014), as seen from the conspicuous fluctuation of currents. This is different from previous studies that suggested that parallel currents are generally uniform across the whole DF layer (e.g., Sun et al, 2013). Figures 3e and 3f show the parallel and perpendicular currents at the DF.…”
Section: 1029/2018gl077928contrasting
confidence: 94%
See 1 more Smart Citation
“…The formation of DFs is associated with unsteady magnetic reconnection (e.g., , spontaneous formation , interchange ballooning instability (e.g., Pritchett & Coroniti, 2010), or jet braking (Birn et al, 2011). The electric field at the DF layer is mainly normal to the DF (Fu et al, 2012b;Sun et al, 2014), and the current is mainly along the DF from dawnside to duskside (Fu et al, 2012b;Sun et al, 2013). Huang, Fu, Vaivads, et al (2015) estimated that the scale of DF in the dawn-dusk direction is about 3.6 R E (R E is Earth's radius).…”
Section: Introductionmentioning
confidence: 99%
“…The current disruption started at the leading edge of the flow, as a sharp dipolarization front (DF) with a magnetic dip ahead of the front layer. The magnetic dip current, which is of Region 2 sense, has been studied recently [Liu et al, 2013a[Liu et al, , 2013bYao et al, 2013b;Sun et al, 2013]. Those studies presented the FAC features ahead of the DF, while this paper has studied the cross-tail current density evolution ahead of earthward flow.…”
Section: Discussionmentioning
confidence: 99%